A phospholipase A1 antibacterial Type VI secretion effector interacts directly with the C‐terminal domain of the VgrG spike protein for delivery. Issue 6 (10th February 2016) - Flaugnatti, Nicolas; Le, Thi Thu Hang; Canaan, Stéphane; Aschtgen, Marie‐Stéphanie; Nguyen, Van Son; Blangy, Stéphanie; Kellenberger, Christine; Roussel, Alain; Cambillau, Christian; Cascales, Eric; Journet, Laure
Summary: The Type VI secretion system (T6SS) is a multiprotein machine that delivers protein effectors in both prokaryotic and eukaryotic cells, allowing interbacterial competition and virulence. The mechanism of action of the T6SS requires the contraction of a sheath‐like structure that propels a needle towards target cells, allowing the delivery of protein effectors. Here, we provide evidence that the entero‐aggregative Escherichia coli Sci‐1 T6SS is required to eliminate competitor bacteria. We further identify Tle1, a toxin effector encoded by this cluster and showed that Tle1 possesses phospholipase A1 and A2 activities required for the interbacterial competition. Self‐protection of the attacker cell is secured by an outer membrane lipoprotein, Tli1, which binds Tle1 in a 1:1 stoichiometric ratio with nanomolar affinity, and inhibits its phospholipase activity. Tle1 is delivered into the periplasm of the prey cells using the VgrG1 needle spike protein as carrier. Further analyses demonstrate that the C‐terminal extension domain of VgrG1, including a transthyretin‐like domain, is responsible for the interaction with Tle1 and its subsequent delivery into target cells. Based on these results, we propose an additional mechanism of transport of T6SS effectors in which cognate effectors are selected by specific motifs located at the C‐terminus of VgrG proteins. Abstract : Entero‐aggregative Escherichia coli uses a Type VI secretion system to deliver the Tle1 phospholipase into competitor bacteria. Self‐protection is secured by Tli1, an outer membrane lipoprotein that binds Tle1 toxin with nanomolar affinity. Tle1 delivery into the periplasm of the prey cells is mediated by a cargo mechanism in which Tle1 directly binds to the VgrG spike C‐terminal extension. This study reveals a new mechanism of effector transport and highlights the versatility of the T6SS.